Numerical Simulation of a Three-Dimensional Fish-Like Body Swimming with Finlets (Communications in Computational Physics, 2020)
The swimming of a 3D fish-like body with finlets is numerically investigatedat Re = 1000 (the Reynolds number is based on the uniform upstream flow and thelength of the fish-like body). The finlets are simply modeled as thin rigid rectangularplates that undulate with the body. The wake structures and the flow around the caudal peduncle are studied. The finlets redirect the local flow across the caudal pedunclebut the vortical structures in the wake are almost not affected by the finlets. Improvement of hydrodynamic performance has not been found in the simulation based onthis simple model. The present numerical result is in agreement with that of the workof Nauen and Lauder [J. Exp. Biol., 204 (2001), pp. 2251-2263] and partially supportsthe hypothesis of Webb [Bull. Fish. Res. Bd. Can., 190 (1975), pp. 1-159].